Kajian Film Assessement “Mereka Bilang Saya Monyet”: A Deconstruction of The Social Order On Female Sexuality - Indiarma, Verani (Jurnal Kaganga: Jurnal Ilmiah Sosial dan Humaniora, 2019)
The purpose of this study is written based on a study that explores transcendent meanings contained in the film text, especially regarding the justification of sexual behaviors of women and men. This study applies a postfeminist deconstruction method. The postfeminist deconstruction discourse proves able to discover the contradictions containing in the text of the film.The results show that there is an attempt by the director to reverse the hierarchical structure of the binary opposition through the movie characters. The female characters seen in the film, is shown as the production of a new meaning of sexuality; women reject the status quo of mainstream sexuality, such as active-passive, wild-civilized, bitch-princess, and so on. In this film, women are allowing themselves to be called a monkey, she is wild or bitch - it is a strategy to oppose the system that has been demanding women to be "nice kids", but, it’s just a mask. There is no female pleasure in this film. This film acknowledges that the look of the women remain the same instead, because the irony in this film is blind.